CLINICAL CHARACTERISTICS AND TREATMENT OF KELOID AND HYPERTROPHIC SCARS USING INTRALESIONAL TRIAMCINOLONE ACETONIDE INJECTION COMBINED WITH FRACTIONAL CO2 LASER THERAPY AT CAN THO DERMATOLOGY HOSPITAL IN 2024-2025 - Le, Thi Kim Chi; Vo, Thi Kim Loan; Doan, Quoc Tuan (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Treatment of keloids and hypertrophic scars remains a challenge for dermatologists. Objectives: To describe the clinical characteristics and evaluate the treatment outcomes of keloids and hypertrophic scars using intralesional triamcinolone acetonide combined with fractional CO₂ laser therapy at Can Tho Dermatology Hospital in 2024-2025. Materials and Methods: A case series study was conducted on 32 patients with keloids and hypertrophic scars treated from May 2024 to February 2025. Results: After 12 weeks of treatment, the mean Vancouver Scar Scale (VSS) score decreased by 3.4±2.3 points, which was statistically significant. Pain is the most common side effect. Conclusion: The combined treatment method demonstrated marked therapeutic efficacy, with a high rate of moderate to good clinical response, suggesting promising potential for managing keloids and hypertrophic scars.